World's Greatest Scientists & Inventors - Wonder House Books (Bharat Wonder Book House, 2023)
A meticulously researched book, which celebrates the achievements of scientists and inventors who have contributed to the development of human society with their talent, hard work and success. Age appropriate content, fun facts and bold illustrations will appeal to the curiosity of young inquisitive minds and help them develop their reading skills and general knowledge.
Keywords: Biographies & Memoirs -- Biographies & Memoirs